Suppression of miR-21 Expression Inhibits Cell Proliferation and Migration of Liver Cancer Cells by Targeting Phosphatase and Tensin Homolog (PTEN) - Liu, Haiwei (Med Sci Monit, 2018)
BACKGROUND: Liver cancer is considered one of the main causes of cancer related deaths across the globe. Moreover, the incidence of liver cancer in developed countries is likely to increase in future. The increase in the incidence of liver cancer, the limited availability of standard treatments, and the side effects of the existing drugs demands exploration and identification of new targets and treatment strategies for liver cancer. In this context, the present study investigated the potential of miR-21 as the therapeutic target for the management of liver cancer. MATERIAL/METHODS: Total RNA was extracted by RNA isolation kit (RNeasy) as per the manufacturer’s instructions. The cDNA synthesis was carried out with the help of RevertAid cDNA synthesis kit (Fermentas). Expression analysis was performed by quantitative RT-PCR. Cell proliferation was examined by CellTiter 96 aqueous one cell proliferation assay kit (Promega) as per manufacturer’s guidelines. Apoptosis was detected by DAPI and Annexin V/PI staining. Cell migration was assessed by wound healing assay. MicroRNA-383 target was delimited by TargetScan software. Protein expression analysis was evaluated by western blotting. RESULTS: Our results revealed that miR-21 was significantly upregulated in liver cancer cells. However, downregulation of miR-21 inhibited cancer cell proliferation, promoted apoptosis, inhibited cell migration, and triggered cell cycle arrest in KYN-2 liver cancer cells. Additionally, in silico analysis revealed PTEN to be the downstream target of miR-21, which was further confirmed by expression analysis through western blotting. CONCLUSIONS: Our results reveal that miR-21 might prove to be an important target for the management of liver cancer.